Festas religiosas na Ilha dos Marinheiros: os ilhéus entre o sagrado e o profano: um estudo fotoetnográfco - Recuero, Carlos Leonardo Coelho (2008)
The following work presents a photoethnographic study about the religious festival of the Ilha dos Marinheiros (Seaman Island). It show the island people devotion to the Cruzade. It also seeks to, through photography and text, narrate the everyday life of the native resident of the island. It also seeks to, through participant observation and the researcher insertion in the community, to verify how the religious festivals, the space, the tradition, the memory and the ethnic question modelate the social fact and structurate the geographically-bounded society. This work presents a society of farmers-fishermans, who love the winds and the seas and the importance of the religious festivals for them. With the photoetnography, method used in this dissertation, we show the fluency of the antropological and ethnographic text, avoiding the imagination of the fact studied and showing photographies.Through these perspectives, the culture and the social organization of the Island is presented and studied.